Clinical approach to palpitations in pregnancy - Ferha Saeed; Kirun Gunganah; Anna S. Herrey (Clinical Medicine)
Palpitations are common in pregnancy and warrant investigation. Palpitations may be caused by non-cardiac and cardiac causes. Patients with structural or functional abnormalities or inherited cardiovascular disease are more likely to develop arrhythmia, especially during pregnancy when the mother’s body undergoes extensive physiological adaptations, which further contribute to an increased arrhythmia risk. While isolated ectopic beats do not require treatment, some heart rhythm disturbances can be life-threatening for mother and baby and mandate prompt intervention.Haemodynamically unstable patients should be electrically cardioverted. If the patient is stable, medical management is indicated, and early involvement of the pregnancy heart team can help facilitate appropriate treatment. In complex arrhythmia, consultation of an arrhythmia expert should be sought . Many anti-arrhythmics are safe in pregnancy, and it is important to reassure the pregnant patient of this.